EU Observatory for Nanomaterials: a constructive view on future regulation - Ponce Del Castillo, Aïda; Krop, Hildo (Brussels, 2017)
"This Policy Brief provides information about the recently established ‘EU Observatory for Nanomaterials’, how it is being developed, its limitations and why it is not an ideal option. It suggests a different monitoring scenario, based on rules which would ensure transparency, improve the ability of national authorities to track different types of nanomaterials along the supply chain, make (nano) information visible, and guarantee an adequate exchange of information on safety at all stages. Finally, it urges policy-makers to make use of foresight and ethics to address fast-moving technological convergence and the new frontiers of science and technology."